Założenia i koncepcja kodyfikacji prawa karnego procesowego w II Rzeczypospolitej - Koredczuk , Józef (PRAWO i WIĘŹ, 2023)
Criminal procedural law is a set of provisions regulating all issues related to the criminal process, particularly defining its model. Criminal procedural law provisions are the most constant and the most crucial element of the criminal trial model. They are generally defined during the development of a given regulation – with regard to criminal procedural law in the Second Polish Republic they were defined by its codification. Despite its shortcomings, the Code of Criminal Procedure of 1928, due to its priority and presented values, is still a model law in historical and comparative research. It was based on the assumptions of the classical school in the study of criminal law. However, its authors also took into account some assumptions of the sociological school. Among contemporary penal procedure codifications, the Code mainly referred to the French Code of Criminal Procedure of 1808. It was the first Polish criminal procedure codification in which the achievements of the Enlightenment and later legal doctrines could be widely used. No wonder all reforms of the criminal procedure after 1945 were based on the Code of 1928. Therefore, among others, it was referred to during the work on the current Code of Criminal Procedure of 1997.